2008
DOI: 10.1002/path.2371
|View full text |Cite
|
Sign up to set email alerts
|

Chronic wound state exacerbated by oxidative stress in Pax6+/− aniridia‐related keratopathy

Abstract: Heterozygosity for the transcription factor PAX6 causes eye disease in humans, characterized by corneal opacity. The molecular aetiology of such disease was investigated using a Pax6+/- mouse model. We found that the barrier function of uninjured Pax6+/- corneas was compromised and that Ca2+-PKC/PLC-ERK/p38 signalling pathways were abnormally activated, mimicking a 'wounded' epithelial state. Using proteomic analysis and direct assay for oxidized proteins, Pax6+/- corneas were found to be susceptible to oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 50 publications
3
45
0
Order By: Relevance
“…The presence of proteins involved in the metabolism of reactive oxygen species, such as peroxiredoxins and catalase in the normal tear film [27] suggests their function in the defense against these highly reactive and toxic compounds. Moreover, oxidative stress has been demonstrated to be a significant factor contributing to chronic wound state and wound-healing delay of corneas in Pax6+/-mouse model [28]. We have found that peroxiredoxin 6 was down-regulated (0.69-fold) in the tears of aniridia patients when compared with healthy family members.…”
Section: Peroxiredoxin-6mentioning
confidence: 50%
“…The presence of proteins involved in the metabolism of reactive oxygen species, such as peroxiredoxins and catalase in the normal tear film [27] suggests their function in the defense against these highly reactive and toxic compounds. Moreover, oxidative stress has been demonstrated to be a significant factor contributing to chronic wound state and wound-healing delay of corneas in Pax6+/-mouse model [28]. We have found that peroxiredoxin 6 was down-regulated (0.69-fold) in the tears of aniridia patients when compared with healthy family members.…”
Section: Peroxiredoxin-6mentioning
confidence: 50%
“…Corneal epithelia, both superficial and basal cells in Pax6 +/-mice, have demonstrated more severe oxidative modifications. 24 The accumulation of oxidized products occurs in parallel with the development of stromal opacities. Oxidative stress keeps Pax6 +/-cells in a chronic wound state, which can trigger nuclear exclusion of Pax6 +/-that has been implicated in transdifferentiation of corneal epithelium into non-corneal phenotype.…”
Section: B Oxidative Stress Wound Healing and Corneal Transparencymentioning
confidence: 99%
“…Pax6 is a nuclear transcription factor, however we have shown that, in common with other transcription factors, it undergoes cytoplasmic shuttling (Camarata et al, 2006;Bimber et al, 2007;Ou et al, 2008). Sox10, which regulates many aspects of embryonic development, and Vax2, which participates with Pax6 in retinal development, both dynamically shuttle between the nucleus and the cytoplasm with consequences for their transcriptional activity (Rehberg et al, 2002;Kim and Lemke, 2006).…”
Section: Pax6 Acts As a Nucleo-cytoplasmic Shuttling Transcription Famentioning
confidence: 99%
“…We previously showed that Pax6 cytoplasmic localisation in the adult corneal epithelium is a consequence of oxidative stress (Ou et al, 2008). In order to analyze if the same mechanism also occurs in Merkel cells, we induced experimental oxidative stress by adding different concentrations of H 2 O 2 to the cell cultures after 4 days in vitro when Pax6 was completely relocated into the cell nuclei.…”
Section: Oxidative Stress Modulates Pax6 Subcellular Localisationmentioning
confidence: 99%